Analysis of The Impact of COVID-19 pandemic on Consumer Satisfaction: A study of McDonald’s Food Delivery - Ng, Jie Yi; Ng, Chiao Qing; Hilmin, Siti Nur; Ng, Chi Yen; Nasharuddin, Naszatul Faizah (International Journal of Tourism and Hospitality in Asia Pasific, 2022)
McDonald's is the world's well-known fast-food corporation. Consequently, McDelivery as a food delivery service has been commonly used and popular in most countries. The objective of this study research is to investigate and analyze the impact of the COVID-19 pandemic on consumer satisfaction towards McDonald’s food delivery. To better understand the findings of the research, an online survey has been carried out to collect the data needed. This survey involved 112 Malaysian and Indonesian respondents and the data were analyzed by the SPSS software. The findings show that perceived usefulness and perceived price are the most significant factors in enhancing customer satisfaction with McDelivery apps and websites. Conversely, the perceived ease of use and perceived trust had no significant impact on customer satisfaction. Keywords: Consumer Behavior, Consumer Satisfaction, COVID-19, Food delivery, McDelivery, Perceived Price, Perceived Usefulness.